Dispositifs pédagogiques dans l’enseignement supérieur et insertion des diplômés - Thierry Chevallier; Jean-François Giret (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This paper studies the effects of higher education teaching and learning practices on the early careers of graduates. It draws on data from a quantitative survey conducted with 11’000 graduates in five European countries and in Japan, five years after graduation. Analysing answers related to the organisation of studies revealed four “pedagogical models”: 1) the traditional academic model, 2) the research-based model, 3) a semi-professional model and 4) a pure professional model. It appears that there is a strong link between education and employment for graduates from programmes classified as professional, whilst research-based programmes are assessed as enabling students to develop higher order skills.